Integrated chemical analysis, metabolic profiling, network pharmacology, molecular docking and toxicity prediction to reveal the active ingredients and their safety of raw and prepared rhubarbs in the treatment of gastric ulcers - Wang, Chenxi; Zhao, Xin; Jiang, Jingjing; Jia, Mengqi; Shi, Wenqing; Wu, Zhenghua; Feng, Shiyu; Fan, Guorong; Lou, Yuefen (Frontiers in Pharmacology, 2024)
Background: Rhubarb, containing raw rhubarb (RR) and two processed products (steamed rhubarb, SR; carbonized rhubarb, CR), is commonly used in high-doses for the treatment of peptic ulcer, especially gastric ulcer (GU). However, their active ingredients, therapeutic targets, and potential mechanism remain unclear. Meanwhile, the safety of these active ingredients is also worth studying.Methods: An offline two-dimensional low-pressure liquid chromatography/high-performance liquid chromatography coupled with high resolution mass spectrometry method was applied to identify the chemical constituents of RR, SR, and CR. Then, the plasma and urine samples of rats after oral administration of RR, SR, and CR were studied for metabolite profiling. Based on the analysis of ingredients in vivo, the key active constituents, core therapeutic targets and key signaling pathways of RR, SR, and CR against GU were screened via network pharmacology and molecular docking. Finally, the efficacy and safety of these key active ingredients were evaluated.Results: Totally, 183, 120 and 115 compounds were identified or tentatively characterized from RR, SR and CR, respectively. Meanwhile, 190, 182 and 180 components were identified after oral administration of RR, SR and CR. By network pharmacology and molecular docking, torachrysone, hydroxyemodin, 6-methylrhein, rhein and emodin anthrone might be the predominant effective constituents in RR, SR, and CR with AKT1 and EGFR being their key targets during the treatment of GU. Moreover, EGFR/PI3K/AKT signaling pathway might play a crucial role in the therapeutic mechanism of GU. In silio ADMET predictions categorized 5 compounds as drugs with good oral bioavailability, but these components may induce liver injury. Conclusions: Overall, our results not only clarified the active substances and molecular mechanism for enhancing our understanding about the traditional efficacy, but also pay attention to the clinical safety issues of raw and prepared rhubarbs.